Interview dos and don'ts - Sleeth, Shannon; Garner, Simon; Video Education Australasia (Australia : Video Education Australasia, 2004)
This program designed to assist young people in understanding the interview process and ensuring they are well prepared for job interviews. The program follows a young man as he applies for a particular job and then follows a process of preparing for, undertaking, and receiving feedback on that interview.
Executive producer, Mark McAuliffe ; camera, Kieran Doolan ; sound, Wayne Martin ; editor, Shannon Sleeth
Voice over : Belinda Kirwan.
DVD format.
Keywords: Employment interviewing; Job interviews; Interviewing; Interviewing -- Technique; Interview